Parental management of self injurious behavior of children with autism - Jamora, Gretel M. (2009)
This study focused on gaining better understanding of parental management of self-injurious behavior of children with autism, and its effect on the family life. A three-part questionnaire was utilized to gather data. The findings showed that the current medical provisions for special children are reactive more than provocative. Stress originating from the home causes stresses among parents the most. While parents recognize the importance of collaborating with professionals for their child's behavior management, they are also inclined to use negative approaches. Care and support groups coming from parents similarly situated and socil organization as well as relaxation and activities play an important role in addressing the parents' physical and emotional challenges in their coping situation.